Marriage Matters Spousal Similarity in Life Satisfaction - Ulrich Schimmack; Richard E. Lucas (Deutsches Institut für Wirtschaftsforschung (DIW), 2006)
Examined the concurrent and cross-lagged spousal similarity in life satisfaction over a 21-year period. Analyses were based on married couples (N = 847) in the German Socio-Economic Panel (SOEP). Concurrent spousal similarity was considerably higher than oneyear retest similarity, revealing spousal similarity in the variable component of life satisfaction. Spousal similarity systematically decreased with length of retest interval, revealing similarity in the changing component of life satisfaction. Finally, there was considerable spousal similarity in the stable component of life satisfaction over 20-years. The implications of these findings for causal theories of life satisfaction and studies in line with behavioural genetics are discussed.
Keywords: Z1; D01; B49; 330; Subjective Well Being; Life Satisfaction; Marriage; Couples; Spousal Similarity; Heritability; Assortative Mating; Longitudinal Panel; SOEP